Adaptation, validation and reliability of the Spanish version of eating pattern inventory for children EPIC-C in a sample of Mexican adolescents - Trujano, Patricia; Gracia, Manuel De; Nava, Carlos; Thomas, Mónica (International Journal Of Community Medicine And Public Health, 2021)
Background: Eating behavior represents an important public health issue. This study shows the results of the adaptation and validation of the questionnaire eating pattern inventory for children (EPI-C) in the Spanish version, what can be very useful in Spanish-speaking contexts. Methods: The adaptation and validation of the questionnaire was carried out with a statistically representative sample of 417 adolescents of Mexico City. Different statistical analysis were applied. Results: The analysis of the adapted version reproduced the same factorial structure and psychometric properties as the original questionnaire. The adapted inventory consisted of 20 items, formed by 4 subscales dietary restraint (8 items), external eating (6 items), parental pressure to eat (3 items), and emotional eating (3 items) which explained the 68,8% of the total variable. Conclusions: The scores of the subscales were associated with the body weight of the adolescents with normal weight and overweight-obesity, with the level of the anxiety state, with the emotional eating and with the dietary restraints which suggests initial evidence of its validity and utility in Spanish speaking countries.